Vagal Neuromodulation in Chronic Heart Failure With Reduced Ejection Fraction: A Systematic Review and Meta-Analysis - Sant'Anna, Lucas Bonacossa; Couceiro, Sérgio Lívio Menezes; Ferreira, Eduardo Amar; Sant'Anna, Mariana Bonacossa; Cardoso, Pedro Rey; Mesquita, Evandro Tinoco; Sant'Anna, Guilherme Mendes; Sant'Anna, Fernando Mendes (Frontiers in Cardiovascular Medicine, 2021)
Objectives: The aim of this study was to evaluate the effects of invasive vagal nerve stimulation (VNS) in patients with chronic heart failure (HF) and reduced ejection fraction (HFrEF). Background: Heart failure is characterized by autonomic nervous system imbalance and electrical events that can lead to sudden death. The effects of parasympathetic (vagal) stimulation in patients with HF are not well-established. Methods: From May 1994 to July 2020, a systematic review was performed using PubMed, Embase, and Cochrane Library for clinical trials, comparing VNS with medical therapy for the management of chronic HFrEF (EF ≤ 40%). A meta-analysis of several outcomes and adverse effects was completed, and GRADE was used to assess the level of evidence. Results: Four randomized controlled trials (RCT) and three prospective studies, totalizing 1,263 patients were identified; 756 treated with VNS and 507 with medical therapy. RCT data were included in the meta-analysis (fixed-effect distribution). Adverse effects related to VNS were observed in only 11% of patients. VNS was associated with significant improvement (GRADE = High) in the New York Heart Association (NYHA) functional class (OR, 2.72, 95% CI: 2.07–3.57, p < 0.0001), quality of life (MD −14.18, 95% CI: −18.09 to −10.28, p < 0.0001), a 6-min walk test (MD, 55.46, 95% CI: 39.11–71.81, p < 0.0001) and NT-proBNP levels (MD −144.25, 95% CI: −238.31 to −50.18, p = 0.003). There was no difference in mortality (OR, 1.24; 95% CI: 0.82–1.89, p = 0.43). Conclusions: A high grade of evidence demonstrated that vagal nerve stimulation improves NYHA functional class, a 6-min walk test, quality of life, and NT-proBNP levels in patients with chronic HFrEF, with no differences in mortality.